How Innovativeness Influence on Women Business Performance - Eviatiwi Kusumaningtyas Sugiyanto; Ratna Wijayanti (Universitas Prasetiya Mulya, 2022)
The problem in this study is that there are still various controversies in the results of research regarding the relationship and influence between innovations on performance. In addition, there is also a gap, namely the increasing number of women's businesses on the one hand and on the other hand, the success of women's businesses tends to be lower than that of men's businesses. So this study aims to close the research gap, namely the influence of Innovativeness on business performance by mediating competitive advantage. The sample is 62 women entrepreneurs. Methods of data collection using a questionnaire via google form. The data analysis method uses SEM with the WrapPLS 7.0 program. The results show that Innovation has a significant positive effect on Competitive Advantage, but has no effect on Business Performance. Meanwhile, Competitive Advantage has a significant positive effect on Business Performance and has succeeded in becoming a mediator (full mediation) for Innovation and Business Performance.